THE INFLUENCE OF FINANCIAL LITERACY AND LOCUS OF CONTROL ON FINANCIAL MANAGEMENT BEHAVIOR IN MICRO, SMALL AND MEDIUM ENTERPRISES IN BIMA CITY - Nurul Huda; Aliah Pratiwi; Aris Munandar; Nafisah Nurul Rahmatia; Fitrianingsih Amalo (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
This study aims to see whether Financial Literacy has an effect on Financial Management Behavior of MSME Actors in Bima City, Does Locus Of Control affect Financial Management Behavior of MSME Actors in Bima City, and which of the variables Financial Literacy and Locus of Control have an influence dominance of Financial Management Behavior in UMKM Actors in the City of Bima. This research was conducted on SMEs in the City of Bima for 6 (six) months. The research method used is explanatory research using a sample survey approach. Conventionally, explanatory research is used to explain the relationship between variables through hypothesis testing. The population in this study was 3,218 MSME actors with a sample of 34 MSME actors in Bima City using a purposive sampling technique, where the questionnaire was tested for validity and reliability and then processed using SPSS so that the accuracy of the analysis tool could be reliable. The results showed that Financial Literacy had an effect on Financial Management Behavior on MSMEs in Bima City while Locus Of Control had no effect on Financial Management Behavior on MSMEs in Bima City. smallest significance (0.000),